Photonic band gap active waveguide filters based on dilute nitrides. Issue 4 (22nd January 2013) - Calò, Giovanna; Grande, Marco; Alexandropoulos, Dimitris; Petruzzelli, Vincenzo
Abstract The wavelength filtering characteristics of active defective Photonic Band Gap (PBG) waveguides based on dilute nitrides are examined. The analyzed structure is made of GaInNAs‐GaInAs MQW ridge waveguides in which a geometrical active defect in the periodic lattice induces selective transmission spectral regions centered at different wavelengths inside the PBG. The device show the advantage of simultaneous DWDM selective filtering and amplification of the filtered signal. The performances of the active PBG filters are investigated as a function of the geometrical and the electrical parameters. The analysis is performed by using proprietary codes, based on the Bidirectional Beam Propagation Method with the Method of Lines introducing the rate equations. Highly selective 9‐channel active filter with minimum value of the bandwidth at half‐height transmittance B3dB=0.12 nm has been calculated. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)